Integrating the Flower and Hayes Cognitive Writing Model into Advanced Arabic Dictation Instruction with AI-Assisted Learning - Aiman; Abdul Nasser Sa'id; Syamsul Arifin (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2026)
This study examines the relevance of the cognitive writing model developed by Linda Flower and John R. Hayes in advanced Arabic dictation instruction and explores the integration of Artificial Intelligence (AI) in supporting cognitive writing processes during orthographic learning. The study is based on the assumption that Arabic dictation (imla’) is not merely a mechanical orthographic exercise, but a cognitive writing activity involving planning, linguistic processing, monitoring, and self-revision throughout the writing process. This research employed a qualitative descriptive-analytical approach through library research by analyzing various studies related to Arabic dictation, cognitive writing processes, the Flower and Hayes model, and AI-assisted language learning. The findings reveal that the stages of planning, translating, and reviewing in the Flower and Hayes model are closely related to orthographic activities in advanced Arabic dictation learning. The planning stage involves orthographic anticipation and linguistic retrieval before writing, the translating stage involves the transformation of mental representation into Arabic graphic forms, while the reviewing stage includes monitoring, evaluation, and orthographic revision. The study also indicates that AI can support these cognitive processes through predictive spelling, contextual prompting, real-time orthographic feedback, and automated revision assistance. Furthermore, AI contributes to the development of metacognitive awareness and self-monitoring during the writing process. This study concludes that integrating the Flower and Hayes cognitive writing model with AI-assisted learning may contribute to the development of more reflective, learner-centered, and cognitively oriented Arabic dictation instruction.